Sociocultural Determinants and Implications of Resistance to COVID-19 Vaccination among Academic Staff of a Nigerian University - Njemanze, Vivian C; Nwosu, Innocent A (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The COVID-19 pandemic has sparked a global effort to develop and distribute vaccines to combat the virus. However, the success of vaccination campaigns hinges on the availability of vaccines and the population’s acceptance and uptake of these vaccines. This study explores the sociocultural factors influencing COVID-19 vaccine resistance among academic staff at Alex Ekwueme University in Nigeria. It also investigated the implications of COVID-19 vaccine resistance among highly educated individuals, who are expected to be at the forefront of vaccine acceptance. A cross-sectional design was employed, and a structured questionnaire was administered to 380 academic staff members. Data was analyzed through descriptive statistics, and hypotheses tested through chi-square revealed a complex interplay of sociocultural factors contributing to vaccine resistance, including concerns about vaccine safety, the influence of social networks and religious beliefs, and reliance on traditional remedies. Furthermore, the study identifies implications of vaccine resistance, such as the continued spread of the pandemic and strain on healthcare resources. Therefore, targeted communication strategies, community engagement, and involvement of key stakeholders are needed to address vaccine hesitancy and promote vaccine acceptance among academic staff and beyond. The Nigerian government should also consider incorporating indigenous remedies in the fight against COVID-19. Ultimately, understanding and addressing sociocultural determinants of vaccine resistance is crucial for effective public health interventions and containment of the pandemic.